Quality of Education Services Against Parental Decisions to Choose Madrasa Ibtidaiyah and the Elementary School at Temanggung Regency. - Oktradiksa, Ahwy; Yoga Santri, Dimas (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2025)
The purpose of this article is to analyze the quality of educational services by parents to choose MI and SD in Temanggung Regency. The facts of the problem are, schools do not have a superior program, schools have not conducted a SWOT test for the dimensions of MI and SD service delivery, cooperation with user partners to oversee the quality of MI and SD is not optimal, schools have not utilized social media or technology as a means of promotional media. This study uses a mix method approach with qualitative and quantitative methods with the type of research correlation of two or more variables between superior educational services and parental decisions, the subjects of this study involved 45 (40 parents and 5 teachers) as samples. The study uses phenomenological facts. The results of the study explain a strong and unidirectional significant relationship between the variables of superior educational services (X1), satisfaction with educational services (X2), and parental decisions (Y) to choose SDN 6 Parakan and MIN 2 Ringianom in Temanggung Regency with the results of the multicollinearity test with a tolerance value of 0.99 greater than 0.10 and VIF less than 10.00, followed by the results of the Spearman rank correlation test with a positive correlation result of 0.673 and a significance value of 0.000 <less than 0.05 or known to be 0.01 which means there is a significant relationship between superior educational services and satisfaction with parental choices in MI and SD Temanggung Regency.